The KIT and PDGFRA switch-control inhibitor DCC-2618 blocks growth and survival of multiple neoplastic cell types in advanced mastocytosis - Schneeweiss-Gleixner, Mathias; Peter, Barbara; Bibi, Siham; Eisenwort, Gregor; Smiljkovic, Dubravka; Blatt, Katharina; Jawhar, Mohamad; Berger, Daniela; Stefanzl, Gabriele; Herndlhofer, Susanne; Greiner, Georg; Hoermann, Gregor; et al. (Haematologica, 2018)
Systemic mastocytosis is a complex disease defined by abnormal growth and accumulation of neoplastic mast cells in various organs. Most patients exhibit a D816V-mutated variant of KIT, which confers resistance against imatinib. Clinical problems in systemic mastocytosis arise from mediator-related symptoms and/or organ destruction caused by malignant expansion of neoplastic mast cells and/or other myeloid cells in various organ systems. DCC-2618 is a spectrum-selective pan KIT and PDGFRA inhibitor which blocks KIT D816V and multiple other kinase targets relevant to systemic mastocytosis. We found that DCC-2618 inhibits the proliferation and survival of various human mast cell lines (HMC-1, ROSA, MCPV-1) as well as primary neoplastic mast cells obtained from patients with advanced systemic mastocytosis (IC50 <1 μM). Moreover, DCC-2618 decreased growth and survival of primary neoplastic eosinophils obtained from patients with systemic mastocytosis or eosinophilic leukemia, leukemic monocytes obtained from patients with chronic myelomonocytic leukemia with or without concomitant systemic mastocytosis, and blast cells obtained from patients with acute myeloid leukemia. Furthermore, DCC-2618 was found to suppress the proliferation of endothelial cells, suggesting additional drug effects on systemic mastocytosis-related angiogenesis. Finally, DCC-2618 was found to downregulate IgE-mediated histamine release from basophils and tryptase release from mast cells. Together, DCC-2618 inhibits growth, survival and activation of multiple cell types relevant to advanced systemic mastocytosis. Whether DCC-2618 is effective in vivo in patients with advanced systemic mastocytosis is currently under investigation in clinical trials.
Pre-published: February 8, 2018
Gesehen am 07.04.2020